Genetic variation of the Plasmodium falciparum circumsporozoite protein in parasite isolates from Homabay County in Kenya - Maina, Michael; Musundi, Sebastian; Kuja, Josiah; Waweru, Harrison; Kiboi, Daniel; Kanoi, Bernard N.; Gitaka, Jesse (Frontiers in Parasitology, 2024)
The Plasmodium falciparum Circumsporozoite Protein (PfCSP) has been used in developing the RTS,S, and R21 malaria vaccine. However, genetic polymorphisms within Pfcsp compromise effectiveness of the vaccine. Thus, it is essential to continuously assess the genetic diversity of Pfcsp, especially when deploying it across different geographical regions. In this study, we assessed the genetic diversity of the Pfcsp on isolates from Homabay County, a malaria-endemic region in western Kenya, and compared it against other isolates from Kenya. We extracted DNA from twentyseven microscopically confirmed P. falciparum positive samples and conducted Illumina sequencing to generate paired-end short reads. The sequences were then mapped to the Pf3D7 reference genome, and genetic variation was analyzed using bcftools. Additionally, we retrieved isolates from two other malaria-endemic regions in Kenya, Kisumu (n=58) and Kilifi (n=596), from MalariaGEN version 7 and compared their genetic diversity and natural selection. We also evaluated the predicted binding affinities for HLA class I and class II supertypes alleles for the identified haplotypes using NetMHCpan and NetMHCIIpan. Our results show the N-terminal of PfCSP was relatively conserved with a notable mutation at A98G across all isolates. Within the central repeat region, the number of NANP repeats varied across the three Kenyan sites. Furthermore, the C-terminal region showed polymorphism within the Th2R and Th3R regions. Haplotype network analysis of the Kenyan isolates revealed 69 haplotypes, with the 3D7 reference being found in the most prevalent haplotype. When assessing the predicted binding affinities between supertypes in HLA Class I and HLA Class II with the identified haplotypes, we observed stronger predicted binding affinities to multiple haplotypes except for the haplotype containing the 3D7 reference. The results suggest the need to take into account the existing changes occurring in Pfcsp while developing malaria vaccines.